Kinerja Organisasi Satuan Kerja Perangkat Daerah dalam Pengelolaan Aset Daerah - Novelis Novelis; Rulinawaty Rulinawaty; Andi Wijaya (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the organizational performance of regional work units in managing regional assets in BPKD Malianau Regency. The research method was carried out qualitatively, using purposive area sampling. The subjects in this research were the Head of BPKD, the Secretary of BPKD Malinau Regency, the Head of BPKD Assets, and the BPKD Staff of Malinau Regency. The research results obtained through a series of in-depth interviews with key informants indicate a significant level of conformity between the program of activities carried out by the Regional Asset Management Sector and the targets and objectives set. The accountability for the Regional Asset Management Sector is created by making a report on the asset manager. Regions to the head of the Agency and the Regional Secretary as property managers, as well as the implementation of asset management by applicable rules and regulations. In conclusion, the organizational performance of regional work units in managing regional assets in BPKD Malianau Regency is good in terms of effectiveness, efficiency, accountability, and transparency. However, there are still some problems in implementation. Keywords: accountability, effectiveness, efficiency and transparency